Comparative study of several PID parameter tuning methods - Zhang, Sai; Hu, Shaolin; Ke, Ye; Chen, Zhihan (SPIE, 2024)
PID (Proportional Integral Derivative) control, as a classical control method, is widely used in petrochemical, metal smelting, food production and other industrial fields due to its superior control performance. With the continuous improvement of industrial production process, the process control environment is becoming more and more complex, and the controlled object often has complex characteristics such as multivariate coupling, large time lag, nonlinearity, multifactor interference, etc. Therefore, the research of PID parameter tuning method has been paid more and more attention, and it has become an important research topic in the field of automatic control. This paper reviews and analyzes Z-N empirical formula method, Critical Ratio method, Cohen-Coon method, ISTE method, fuzzy algorithm and adaptive particle swarm optimization (APSO) algorithm several PID parameter tuning methods, and applies the MATLAB software to analyze the effect of different tuning methods on the performance of the system through the simulation of Simulink comparison experiments. In this paper, the second-order system is used as the control object, and the experimental results show that the APSO PID parameter self-tuning is better than the other methods in the experiments of response performance analysis, tracking performance analysis, and robustness analysis in terms of rise time, overshooting amount, stabilization time and robustness, all of them are better than the other methods.